Political Economy of Exclusion: State-Based Incitement of Intolerance as a Distraction from a Downturn in the Economy. Issue 2 (June 2021) - Shehadeh, Lana; Lai, Qing
Abstract: Middle East scholars have traditionally attributed the survival of monarchs in the Gulf to the use of financial appeasements fueled by oil revenues. With rampant political insecurity in the region and the revolutionary fervor present after the Arab Spring, leaders have gone beyond the traditional rentier state system to ensure political survival by playing on the sentiments of sectarianism and identity politics. This paper argues that religious sectarianism is not only a question of attitudes and sentiments toward a religious minority but also a politically motivated state mechanism used to maintain the status quo and ensure an extended legitimation of power. We argue that the state often capitalizes on people's fear of economic adversities to incite sectarian exclusions of religious minorities, this is especially evident in times of economic hardships. With survey data from the Arab Barometer, we examined such political psychology in Saudi Arabia in 2011, at the onset of the Arab Spring. We found that Sunni Muslim sentiments of sectarian exclusion toward the Shi'a minority could be attributed to not just religiosity but also state crafted incitement by the Saudi government. In particular, our results show that state-based sectarian intolerance was in part fueled by the government's scapegoating of the Shi'a communities during times of economic downturns.